A Comparative Study of the Effects of Oxygen Ions Upon the Free Volume and Physico‐Chemical Properties of Makrofol (KG & N) Polycarbonate. Issue 1 (November 2015) - Gupta, Sanjeev Kumar; Singh, Paramjit; Awasthi, K.; Roychowdhury, A.; Kumar, Rajesh
Summary: Makrofol (KG & N) polymers are the important class of polycarbonates which are used as solid state nuclear track detectors. The effect of 100 MeV oxygen ions (O 7+ ) on the free volume and physico‐chemical properties of Makrofol (KG & N) polymers were studied. The pristine and irradiated samples were characterized by positron annihilation lifetime spectroscopy, X‐ray diffraction, UV‐visible and FTIR. A comparative study of free volume was carried out from the obtained values of the pristine and irradiated samples of both the polymers. The absorption edges of UV‐visible were found to be shifted towards longer wavelength region. The intensities of the various absorption bands of the infrared spectra were found to be modified; which indicated the changes in the chemical properties of the exposed samples.